Fourier transform infrared and resonance raman studies of the interaction of azide with cytochrome c oxidase from paracoccus denitrificans - Vamvouka, Magdalini; Müller, Werner; Varotsis, Constantinos (My University, 1999)
The interaction of azide with oxidized cytochrome c oxidase from Paracoccus denitrificans has been studied by resonance Raman, Fourier transform infrared, and UV - vis spectroscopy. Azide binds in two phases: a high-affinity phase (K d = 4.1 μM) in which it is bound to a nonmetal site near the binuclear center and a low-affinity phase (K d = 11.4 mM) in which it is bound as a bridge to the binuclear center. The resonance Raman spectra of the low-affinity phase display one isotope-dependent vibrational mode at 417 cm -1. The FTIR spectra display two isotope-dependent bands at 2038 and 2056 cm -1. We assign the band at 417 cm -1 to ν(Fe-N 3-Cu B) and the bands at 2038 and 2056 cm -1 to ν as(N 3). We observe similar FTIR spectra for the azide complex of bovine heart oxidase and conclude that the binuclear center in this oxidase behaves in a manner analogous to the P. denitrificans enzyme. In contrast to mammalian cytochrome c oxidase (Li, W.; Palmer, G. Biochemistry 1993, 322, 1833-1843), the low-affinity phase observed in the interaction of azide with the P. denitrificans enzyme is not associated with binding of azide to heme a. The observation of two FTIR ν as(N 3) modes suggests that the azide ion binds to two different enzyme conformations, both forming bridging complexes with the binuclear center. Comparison of the UV-vis, resonance Raman, and FTIR data of the azide-bound cytochrome c aa 3 from P. denitrificans and those of azide-bound quinol cytochrome bo 3 suggest significant alterations in the interaction of azide with the oxidized forms of these bacterial oxidases resulting from specific structural differences within their respective heme a 3-Cu B and heme o 3-Cu B binuclear pockets
Keywords: Fourier transform infrared spectroscopy; Azides; Cytochrome oxidase; Heme; Enzymes; Chemistry